Combined Task and Motion Planning for Mobile Manipulation - Wolfe, Jason; Marthi, Bhaskara; Russell, Stuart (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
We present a hierarchical planning system and its application to robotic manipulation. The novel features of the system are: 1) it finds high-quality kinematic solutions to task-level problems; 2) it takes advantage of subtask-specific irrelevance information, reusing optimal solutions to state-abstracted subproblems across the search space. We briefly describe how the system handles uncertainty during plan execution, and present results on discrete problems as well as pick-and-place tasks for a mobile robot.